ZŁE TRAKTOWANIE DZIECKA W EUROPEJSKIEJ KARCIE SPOŁECZNEJ ORAZ KONWENCJI O OCHRONIE PRAW CZŁOWIEKA I PODSTAWOWYCH WOLNOŚCI - Łasak, Katarzyna (Wydział Prawa i Administracji UAM, 2007)
In the Charter1, the Revised Charter2 and in the Convention3, a child means every human being below the age of eighteen. The age o f a child is a reason o f his/her vulnerability to ill-treatment. These treaties endeavour to protect a child against bad treatment, albeit to different degrees and by various means. Article 3 of the Convention secures a child from extreme forms of physical and mental abuse,which include torture, inhuman or degrading treatment or punishment. In its system the Charter had adopted this understanding o f prohibition of a child’s ill-treatment and then adapted it to suit its own purposes and uses. In its current form, the prohibition in the Charter and the Revised Charter should be interpreted in two ways. In its essence, it prohibits any form of violence against a child, while in its expanded formula it provides that the childs legal status, health, education, or financial provision, nor the right to rehabilitation o f juvenile offenders, should be neglected. This other aspect of the prohibition of ill-treatment under the system of the Charter is also present in the Convention, although reduced to the dimension of the first generation of human rights. Moreover, its efficiency is further limited due to the specific features of the implementation mechanism.
PROHIBITION OF CHILD’S ILL-TREATMENT: EUROPEAN SOCIAL CHARTER AND CONVENTION FOR THE PROTECTION OF HUMAN RIGHTS AND FUNDAMENTAL FREEDOMS